THE LEARNING MANAGEMENT IN THE HISTORY SUBJECT ON THE DEVELOPMENT OF THE SUKHOTHAI KINGDOM USING BRAIN-BASED LEARNING CONCEPTS WITH METAVERSE FOR THE FIRST YEAR SECONDARY SCHOOL STUDENTS AT KHOK SI PHITTHAYASAN SCHOOL, MUEANG DISTRICT, KHON KAEN PROVINCE - Wantapho, Natdanai; Ruangsan, Niraj; Saengsai, Prayoon; Huschaiyo, Chaichet; Ruangsomsri, Nisarat (Journal of Buddhist Education and Research (JBER), 2024)
This research aimed to 1) study the conditions and learning management approaches, 2) determine the efficiency of learning management, 3) compare the learning achievement, and 4) assess the students' satisfaction with learning management. The target group for this research was 32 of 1/1 students at Khok Si Phitthayasan School, Mueang District, Khon Kaen, enrolled in the first semester of the 2023 academic year, selected via simple random sampling. The tools used included 1) a learning management condition questionnaire, 2) an interview form, 3) a lesson plan, 4) a pre-and post-learning achievement test, 5) Metaverse media, and 6) a student satisfaction questionnaire. The statistical methods used for analysis were the mean, standard deviation, and significant statistics at the .05 level, along with calculating the efficiency value (E1/E2) using statistical software. The research results were as follows: 1) The condition of learning management in the history subject on the development of the Sukhothai Kingdom using brain-based learning concepts with Metaverse for the first-year secondary school students at Khok Si Phitthayasan School was overall at a high level. 2)The efficiency analysis of learning management in the history subject on the development of the Sukhothai Kingdom using brain-based learning concepts with Metaverse for first-year secondary school students at Khok Si Phitthayasan School had an efficiency of 86.70/84.38, meeting the 80/80 criteria. 3)The comparison of learning achievement in the history subject on the development of the Sukhothai Kingdom between pre-learning and post-learning using brain-based learning concepts with Metaverse for first-year secondary school students at Khok Si Phitthayasan School showed significantly higher post-learning scores at the .05 level. 4) The student satisfaction analysis with learning management in the history subject on the development of the Sukhothai Kingdom using brain-based learning concepts with Metaverse for first-year secondary school students at Khok Si Phitthayasan School was at the highest level.